Adventitial remodeling protects against aortic rupture following late smooth muscle-specific disruption of TGFβ signaling. (April 2021) - Kawamura, Y.; Murtada, S.-I.; Gao, F.; Liu, X.; Tellides, G.; Humphrey, J.D.
Abstract: Altered signaling through transforming growth factor-beta (TGFβ) increases the risk of aortic dissection in patients, which has been confirmed in mouse models. It is well known that altered TGFβ signaling affects matrix turnover, but there has not been a careful examination of associated changes in structure-function relations. In this paper, we present new findings on the rupture potential of the aortic wall following late postnatal smooth muscle cell (SMC)-specific disruption of type I and II TGFβ receptors in a mouse model with demonstrated dissection susceptibility. Using a combination of custom computer-controlled biaxial tests and quantitative histology and immunohistochemistry, we found that loss of TGFβ signaling in SMCs compromises medial properties but induces compensatory changes in the adventitia that preserve wall strength above that which is needed to resist in vivo values of wall stress. These findings emphasize the different structural defects that lead to aortic dissection and rupture – compromised medial integrity and insufficient adventitial strength, respectively. Relative differences in these two defects, in an individual subject at a particular time, likely reflects the considerable phenotypic diversity that is common in clinical presentations of thoracic aortic dissection and rupture. There is, therefore, a need to move beyond examinations of bulk biological assays and wall properties to cell- and layer-specific studies that delineate pathologic and compensatory changes in wall biology and composition, and thus the structural integrity of the aortic wall that can dictate differences between life and death. Graphical abstract: Image 1 Highlights: TGFβ pathway disruption in vascular SMC drives medial degeneration reducing strength. Compensatory changes in adventitia augment wall strength and prevent aortic rupture. Adventitial collagen density and fiber thickness underlie altered matrix properties. Medial defects drive aortic dissection, adventitial defects lead to aortic rupture.